622.692 APPLICATION OF EFFECTIVE METHODS IN THE TRANSPORTATION OF HIGH-VISCOSITY OILS - Sattorov, Mirvohid; Yamaletdinova, Aygul (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Abstract: Objective. The article examines the effect of various components and the addition of chemical reagents (depressant additives) to improve the flowability of paraffin oils. The introduction of the additive significantly changes the crystallization process in paraffin oils. The development and application of new, more efficient and cheaper additives significantly contribute to the technological progress of pipeline transport of high-paraffin oils and heavy oil products. All these measures will reduce the wear and tear of equipment during transport and increase economic performance. Methods. The paper used methods to determine the surface tension, component composition, density and dynamic viscosity of oil. Results. The addition of temperature and chemical reagent in paraffin and high paraffin oils has resulted in reduced viscosity and thus increased oil transport capabilities. Conclusion. Reagents are used to reduce the viscosity and solidification temperature during oil extraction and transportation. When used as an additive for pipeline transport, the coagulation regulator reduces the working and starting pressure of oil pipelines, as well as the energy consumption to drive oil.